Students’ Perception on Jigsaw Strategy in English Teaching and Learning Activities - Habiburrahman, Muhammad; Dwinalida, Khairunnisa (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2024)
Jigsaw is a simple cooperative teaching strategy that can make students interested in learning activities. This study investigated tenth-grade students' perceptions of the jigsaw strategy as a teaching and learning approach at MA Al Hikmah 1 Brebes. Mixed method which including both quantitative and qualitative design were applied in this current research. Quantitative data were collected through questionnaires administered to 75 students, followed by qualitative data through interviews. Findings revealed that students generally held positive views of the jigsaw strategy, perceiving it as an effective tool for improving comprehension, fostering collaboration, and enhancing active learning. However, challenges related to implementation, such as time constraints and teacher preparation, were identified. The conclusion of this study is that the Jigsaw strategy can be an effective alternative to improve student motivation and learning outcomes in learning English.